1) x² + 3x – 10= 0
(Por factorización)
(-2) (5) = -10
(-2) + 4= 3
(X+5) (x – 2) = 0
x1= -5 x2= -2
2) a² + 4ª + 3= 0
(Por fórmula general)
X= -b±√b² - 4ac
——————
2a
a= 2 b= 4 c= 5
-(4)±√(4)² - 4 (1) (3)
————————
2 (2)
-4√16 – 12 = -4= √4
——
2
-4±2 -4+1 -2
—— = ——— = —— = 1
2 2 2
X1= 1
-4 -2 46
— = —— = -3
2 2
X2= -3
3) y² - 9y + 20= 0
(completar el trinomio cuadrado perfecto)
4² - 9y + 20= 0
4² - 9y= - 2 – 0
4² - 9y – (9/2)²= -20 – (9/2)²
√(y – 9/2)²= 20 – (81/2) = 80- 81/8) = 1 / 2
Y= - 9/2 – 1/ 2
X1= 9/2 + 1 / 2= 10/2= 5
X1= 5
X2= 9/2 – 1 / 2= 8/2= 4
X2= 4
4) m² + 5m – 14= 0
(Por factorización)
M (7) x (- 2) = -14
(7) – (-2) = 5
(m+7) (m-2)
M+7= 0 ; m-2= 0
M= -7 ; m=+2
5) a² + 4a+ 3= 0
(Por factorización)
(3) (1) = 3
3+1= 4
(a= -3) (a+1)= 0
a= -3 ; a= -1
No hay comentarios:
Publicar un comentario